A Case Report of Clinical Features Analysis of a Novel IKBKG Variant Leading to Anhidrotic Ectodermal Dysplasia and Immunodeficiency - HUANG Xiaomei; LUO Ying; HE Tingyan; XU Yongbin; XIA Yu; YANG Zhi; ZHU Xiaona; HUANG Yanyan; WENG Ruohang; YANG Jun; WANG Linlin (罕见病研究)
IKBKG is the essential modulator for nuclear factor-κB(NF-κB) signaling pathway, and mutations within this gene can lead to anhidrotic ectodermal dysplasia and immunodeficiency (EDA-ID). Here we report a male patient, who presented with mild frontal bossing, sparse hair, skin pigmentation, conical teeth, and recurrent infections involving bacteria, fungi, and viruses after one month of age, together with hypogammaglobulinemia. These symptoms were consistent with the phenotype of EDA-ID. Genetic analysis revealed a hemizygous mutation c.1249T > G (p.Cys417Gly) in exon 10 of the IKBKG gene in the patient. The mother of the patient was identified as heterozygous carriers of the same mutation. Immunological assessment revealed a significant reduction in memory B cells. The patient showed no skewed TCR diversity. PHA-induced T-cell proliferation was impaired. IFN-γ secretion by Th cells was significantly reduced after PHA stimulation. IκBα degradation rate retained the same in the patient. We summarized the clinical features of the patient and conducted immunological analysis, in order to increase pediatricians′awareness of this rare disease. For boys with early-onset recurrent infections together with ectodermal dysplasia, IKBKG mutation should be considered. In addition, genetic analysis is needed to exclude pseudogene interference and functional evaluations are required.